2016
DOI: 10.1186/s12995-016-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Kinaesthetics care conception during patient handling on the development of musculoskeletal complaints and diseases – A scoping review

Abstract: The Kinaesthetics care conception is a nursing approach for patient handling which aims to prevent work-related complaints and diseases. The evidence about the influence of Kinaesthetics on musculoskeletal disorders among persons who handle patients is unclear to date. The purposes of the scoping review are to gain insight into the current state of research regarding the clinical effectiveness of Kinaesthetics (in terms of perceived exertion and musculoskeletal complaints) among persons who handle patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…23 reviews on workplace interventions for the prevention and improvement of musculoskeletal disorders were identified [3,5,8,9,10,11,34,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. In these reviews, 407 individual studies were summarized, predominantly evaluating behavioral preventive interventions, such as training and education, exercise programs, and ergonomic interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 reviews on workplace interventions for the prevention and improvement of musculoskeletal disorders were identified [3,5,8,9,10,11,34,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. In these reviews, 407 individual studies were summarized, predominantly evaluating behavioral preventive interventions, such as training and education, exercise programs, and ergonomic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Improving working conditions may promote physical and mental health by combining both the individual and organizational level. A number of reviews and single studies have addressed the efficacy and cost-effectiveness of well-designed worksite health promotion programs to improve the health of employees and save money for employers [2,3,4,5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that despite many positive effects perceived from other WHPPs, participation rates are critically low [25,26]. WHPPs have positive effects on employee behaviours (in terms of encouraging regular physical activity, healthy eating, stress management, sleep hygiene, and healthy relationships) which increase personal resiliency and improve health [19,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The potential strength of the STAR-VITAL program is that it addresses multiple variables in the work environment (work-related health risks) and behavioural habits (physical activity and eating habits) of employees in SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…A technology-supported measurement system could therefore help to improve the situation. In addition to the validity of the measurement, a particular [1] One meta-study showed zero to only small effects [14], although few controlled studies show effects for single body regions or specific training approaches [15,16]. challenge is the special requirements placed on the measurement system in everyday working life.…”
Section: Introductionmentioning
confidence: 99%